Politics, Biosecurity, Olympic and Paralympic Games Tokyo 2020 (Research, Society and Development, 2021)
The Olympics and Paralympics are eagerly awaited by everyone. It is simply the biggest sporting event in the world, which brings together thousands of athletes from hundreds of different countries and have been hit hard by the COVID-19 Pandemic. Nobody thought that biological actions, SARS-CoV-2, could change the entire global sport scenario. Thus, the study proposed to discuss politics, biosafety and the holding of the Olympic and Paralympic Games. Despite the vaccination campaigns, the world is still under the COVID-19 pandemic. Tokyo is currently in a state of emergency. By the end of the games, what will leave the biggest mark, the larger access to vaccination from the rich countries, which should hold the largest number of medals, or the political interventions by institutions that have commercial interests in Tokyo 2020?